Vanadium(III)--cysteine enhances the sensitivity of murine breast adenocarcinoma cells to cyclophosphamide by promoting apoptosis and blocking angiogenesis - Abhishek Basu; Arin Bhattacharjee; Rathindranath Baral; Jaydip Biswas; Amalesh Samanta; Sudin Bhattacharya (Tumor Biology)
Various epidemiological and preclinical studies have already established the cancer chemopreventive potential of vanadium-based compounds. In addition to its preventive efficacy, studies have also indicated the abilities of vanadium-based compounds to induce cell death selectively toward malignant cells. Therefore, the objective of the present investigation is to improve the therapeutic efficacy and toxicity profile of an alkylating agent, cyclophosphamide, by the concurrent use of an organovanadium complex, vanadium(III)- l -cysteine. In this study, vanadium(III)- l -cysteine (1 mg/kg body weight, per os) was administered alone as well as in combination with cyclophosphamide (25 mg/kg body weight, intraperitoneal) in concomitant and pretreatment schedule in mice bearing breast adenocarcinoma cells. The results showed that the combination treatment significantly decreased the tumor burden and enhanced survivability of tumor-bearing mice through generation of reactive oxygen species in tumor cells. These ultimately led to DNA damage, depolarization of mitochondrial membrane potential, and apoptosis in tumor cells. Further insight into the molecular pathway disclosed that the combination treatment caused upregulation of p53 and Bax and suppression of Bcl-2 followed by the activation of caspase cascade and poly (ADP-ribose) polymerase cleavage. Administration of vanadium(III)- l -cysteine also resulted in significant attenuation of peritoneal vasculature and sprouting of the blood vessels by decreasing the levels of vascular endothelial growth factor A and matrix metalloproteinase 9 in the ascites fluid of tumor-bearing mice. Furthermore, vanadium(III)- l -cysteine significantly attenuated cyclophosphamide-induced hematopoietic, hepatic, and genetic damages and provided additional survival advantages. Hence, this study suggested that vanadium(III)- l -cysteine may offer potential therapeutic benefit in combination with cyclophosphamide by augmenting anticancer efficacy and diminishing toxicity to the host.